Is UV/Ce(iv) process a chloride-resistant AOPs for organic pollutants decontamination?. Issue 96 (30th September 2016) - Liu, Wenqian; Fang, Changling; Huang, Ying; Ai, Luoyan; Yang, Fei; Wang, Zhaohui; Liu, Jianshe
Abstract : Negligible AOX formation is observed in UV/Ce(iv )/Cl − process due to the varied reaction pathways in the presence of chloride. Abstract : Most of the current advanced oxidation processes (AOPs) are vulnerable to the presence of chloride in saline wastewater treatment because chloride not only affects the degradation kinetics but also probably leads to absorbable organic halogen (AOX) formation. Here we report an UV/Ce(iv ) process can efficiently oxidize organic pollutants such as Acid Orange 7, even in the presence of chloride. Fluorescent probe technology suggests hydroxyl radicals were generated in UV/Ce(iv ) process, but not in UV/Ce(iv )/Cl − system. In the presence of chloride, Ce(iv )–chloride complex was formed, which can directly oxidize dyes or generate reactive oxygen species by chlorine activation. Although degradation and mineralization rates of dyes were still inhibited to some extents by large amounts of chloride, but negligible AOX was generated. Therefore, UV/Ce(iv ) process can be recommended as an alternative AOPs when treating acidic saline wastewater.